The Effect of Motivation and Career Development on Employee Job Satisfaction of PT. Pawn (Persero) Regional Office I Medan - Karishdian Zulkarnain; Kiki Farida Ferine (International Journal of Society and Law, 2024)
Employee job satisfaction is one of the important aspects in every company. Employee job satisfaction occurs because of the motivation in employees in carrying out all their work. And also because of the career development opportunities offered by the company. This study aims to analyze and get answers whether the variables of motivation and career development have a partial and simultaneous effect on the job satisfaction of employees of PT. Pegadaian (Persero). This approach uses a quantitative approach with a total of 30 respondents. Testing was carried out using SPSS ver 29. The results showed that motivation (X1) had a positive and significant effect on job satisfaction (Y) while career development (X2) had no positive and significant effect on job satisfaction (Y). However, motivation (X1) and career development (X2) have a simultaneous effect on job satisfaction (Y)